Water-soluble polymers comprising hydroxamic acid groups
By using water-soluble polymers with specific backbone and polyether side chain structures as dispersants, the problem of low dose efficiency of conventional dispersants in natural gypsum sources containing clay minerals is solved, and an efficient solidification process is achieved and the production efficiency of gypsum wall panels is improved.
Patent Information
- Application Number
- CN202380066237.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-16
- Filing Date
- 2023-09-07
- Publication Date
- 2025-04-25
AI Technical Summary
Prior Art When using natural gypsum sources containing clay minerals and other impurities, the low dose efficiency of conventional dispersants leads to a delay in the solidification process, affecting the production of gypsum siding.
A water-soluble polymer is used, which comprises a backbone and a polyether side chain consisting of a carbon chain having at least 16 carbon atoms to which the hydroxamic acid group or a salt thereof is attached as a dispersant in the inorganic particle composition.
The water-soluble polymer exhibits high dose efficiency in the inorganic particle composition, reduces retarding during solidification, improves the production efficiency of gypsum siding, and is effective in both calcium sulfate adhesives containing and without clay mineral impurities.
Smart Images

Figure BDA0005311950570000041 
Figure BDA0005311950570000051 
Figure BDA0005311950570000091
Abstract
Description
[0001] The present invention relates to a water-soluble polymer comprising a main chain consisting of a carbon chain having at least 16 carbon atoms and polyether side chains, wherein hydroxamic acid groups or salts thereof are attached to the main chain.
[0002] Also disclosed is an inorganic particle composition comprising the water-soluble polymer. Another aspect of the present invention is the use of the water-soluble polymer of the present invention as a dispersant in an inorganic particle composition.
[0003] Polyacrylates, lignin sulfonates, melamine sulfonates, polycarboxylic acid ethers and naphthalene sulfonates are very widely used as dispersants (flow agents) for inorganic particulate compositions. One major application area is the formulation of building chemicals, with the aim of reducing the water requirement of an otherwise identical composition or improving the processability of an otherwise identical composition. Other application areas are inorganic pigment compositions, which contain dry-ground minerals, usually metals and metal salts, and are generally used to provide color in many applications.
[0004] All the dispersants mentioned are polyelectrolytes which, due to their charge carriers in the polymer, are adsorbed on the surface of the inorganic particles, as a result of which the surface charge of the particles is changed (electrostatic dispersion mechanism). Comb polymers (polycarboxylate ethers) comprise a main chain ("backbone") along which functional groups capable of adsorption (usually carboxylates) are arranged and side chains, and in contrast to the other dispersants mentioned, also comprise side chains consisting, for example, of uncharged hydrophilic ethylene oxide units. These side chains occupy a large amount of space (high steric demand) and therefore have an additional influence on the dispersing action (steric dispersion mechanism). The polymers adsorb via their anionic groups onto the positively charged regions of the particles, while the side chains extend into the pores filled with the mixing water and in this way inhibit the agglomeration of the solid particles by steric hindrance, which is responsible for the dispersing action. Up to the so-called saturation dose, the dispersing action of the dispersant (which can be measured, for example, by the slump) increases with increasing addition or amount of adsorbed polyelectrolyte.
[0005] Conventional examples of superplasticizers used with gypsum are melamine sulfonate-formaldehyde condensation products (MFS) and beta-naphthalene sulfonate-formaldehyde condensation products (BNS). The preparation and use of BNS are well known and disclosed in EP 0 214 412 B1 and DE 2 007 603 C1. The preparation and use of MFS are also well known in the art. MFS dispersants are disclosed, for example, in DE 4411 797 A1, DE 195 38 821 A1 and EP 0 059 353 B1.
[0006] The use of copolymers based on polycarboxylic acid ethers as plasticizers and consistency retainers for calcium sulfate-based binders is also well known. Such copolymers consist essentially of ethylenically unsaturated monocarboxylic acid comonomers or their esters or salts and / or ethylenically unsaturated sulfonic acid comonomers together with comonomers having polyether functionality.
[0007] However, typical commercially available natural gypsum sources often contain up to 20% or more clay minerals and other impurities which result in reduced calcium sulfate levels.
[0008] Clay is a common name for a number of fine-grained earthy materials that become plastic when wetted and are composed primarily of phyllosilicate minerals that contain varying amounts of water in the mineral structure. There are many known types of clay minerals. Some of the more common types are: kaolinite, illite, chlorite, vermiculite, and smectite (also known as montmorillonite), the latter two of which have a pronounced ability to absorb water.
[0009] Chemically, clays are hydrated aluminum silicates, usually containing alkali metals, alkaline earth metals and / or iron. Clay minerals consist of interconnected sheets of silicate combined with a second sheet of material consisting of metal atoms, oxygen and hydroxyls, forming a double-layer mineral, such as in kaolinite. The latter sheet structure is sometimes found sandwiched between two silica sheets, forming a triple-layer mineral, such as in vermiculite. Structurally, clay minerals consist of planes of cations arranged in sheets, which can be tetrahedral or octahedral coordinated (with oxygen), which in turn are arranged in layers, the layers usually being described as 2:1 if they involve units consisting of two tetrahedral sheets and one octahedral sheet, or 1:1 if they involve units consisting of alternating tetrahedral sheets and octahedral sheets. In addition, some 2:1 clay minerals have interlayer sites between consecutive 2:1 units, which can be occupied by interlayer cations, usually hydrated. Clay minerals are divided into layer types, and within layer types, into groups based on charge x per formula unit (Guggenheim S. et al., Clays and Clay Minerals, 54(6), 761-772, 2006). Charge x per formula unit is the net negative charge per layer, expressed as a positive number. Further subdivisions of subgroups are based on dioctahedral or trioctahedral character, and finally on species of chemical composition, e.g.
[0010] x≈0: pyrophyllite-like
[0011] x≈0.2-0.6: Smectite, such as montmorillonite, nontronite, talc or hectorite
[0012] x≈0.6-0.9: Vermiculite-like
[0013] x≈1.8-2: brittle mica, such as green brittle mica, barium iron brittle mica, and barium magnesium brittle mica.
[0014] Conventional dispersants used in gypsum compositions generally achieve good water reduction when using pure gypsum sources such as flue gas desulfurization gypsum (FGD gypsum), however, in natural gypsum sources containing clay minerals and other impurities, conventional dispersants have low dosage efficiency and require adjustment of the amount of dispersant for specific applications. However, additional amounts of dispersants retard the crystallization of calcium sulfate dihydrate and thus have an adverse effect in many applications, such as in the production of gypsum wallboard.
[0015] It is also common practice to use dispersants to help stabilize aqueous suspensions of pigments. Inorganic pigments are usually composed of dry-ground minerals, usually metals and metal salts, and are commonly used to provide color in many applications. Typical applications include the manufacture of many products, such as paper, card or other paper products, plastics, paints or other coatings. Aqueous dispersions of pigments are often used to improve the mechanical and optical properties of the products to which they are applied.
[0016] A variety of dispersants are known for dispersing and / or stabilizing aqueous suspensions of pigments to reduce or prevent the sedimentation of pigment particles in the suspension. Such dispersants include, for example, silicates or phosphates, phosphonates or oligomeric substances with functional groups.
[0017] In general, there is an increasing demand to provide aqueous inorganic pigment slurries that combine high solids with low viscosity.
[0018] Therefore, an object of the present invention is to provide a dispersant with high dosage efficiency for inorganic particle compositions, especially inorganic binder or inorganic pigment compositions. A secondary object of the present invention is to provide a dispersant for binder compositions, wherein the dispersant provides high dosage efficiency in calcium sulfate binders with and without clay mineral impurities. At the same time, another object is to provide a dispersant that will also reduce the retardation in inorganic binder systems compared to polycarboxylic acid ethers. Another object of the present invention is to provide a dispersant that can make high solids aqueous slurries of inorganic pigments exhibit acceptable or lower viscosity. Another important object is to achieve acceptable or improved solids content, have acceptable or improved viscosity, and improve the stability of the slurry.
[0019] The object of the present invention is to solve the problem by a water-soluble polymer comprising
[0020] a) a main chain consisting of a carbon chain having at least 16 carbon atoms, and
[0021] b) polyether side chains,
[0022] Characterized in that a hydroxamic acid group or a salt thereof is attached to the main chain.
[0023] In a preferred embodiment, the polyether group of the at least one water-soluble polymer is a polyether group of structural unit (I),
[0024] *-U-(C(O)) k -X-(AlkO) n -W(I)
[0025] in
[0026] * indicates the bonding site with the acid group-containing polymer,
[0027] U is a chemical bond or an alkylene group having 1 to 8 carbon atoms,
[0028] X is oxygen, sulfur or the group NR 1 ,
[0029] k is 0 or 1,
[0030] n is an integer, based on the acid group-containing polymer, whose average value is in the range of 3 to 300,
[0031] Alk is a C2-C4 alkylene group, and in the group (Alk-O) n In, Alk can be the same or different,
[0032] W is hydrogen, C1-C6 alkyl or aryl, or a group YF, wherein
[0033] Y is a straight or branched chain alkylene group having 2 to 8 carbon atoms and may have a benzene ring,
[0034] F is a 5- to 10-membered nitrogen heterocycle which is bonded via the nitrogen and which, as ring members, in addition to the nitrogen and carbon atoms, may also have 1, 2 or 3 additional heteroatoms selected from oxygen, nitrogen and sulfur, the nitrogen ring members may have radicals R 2 , and 1 or 2 carbon ring members may be present in the form of a carbonyl group,
[0035] R 1 is hydrogen, C1-C4-alkyl or benzyl, and
[0036] R 2 It is H, C1-C4 alkyl or benzyl.
[0037] In a preferred embodiment, the water-soluble polymer is a copolymer comprising structural unit (Va)
[0038]
[0039] in
[0040] R 3 and R 4are independently hydrogen, an aliphatic hydrocarbon group having 1 to 20 carbon atoms, an alicyclic hydrocarbon group having 5 to 8 carbon atoms or an optionally substituted aryl group having 6 to 14 carbon atoms,
[0041] R 5 It is H, -COOM a 、-CO-NH-(OM a )、-CO-O(C q H 2q O) r -R 3 、-CO-NH-(C q H 2q O) r -R 3
[0042] M is hydrogen, a monovalent, divalent or trivalent metal ion, an ammonium ion or an organic amine group
[0043] a is 1 / 3, 1 / 2, or 1
[0044] q occurs at every occurrence and for every (C q H 2q O) units are independently 2, 3 or 4 in the same or different manner, and
[0045] r is 0 to 200.
[0046] In particular, M is hydrogen, a monovalent, divalent or trivalent metal ion, preferably a sodium ion, a potassium ion, a calcium ion or a magnesium ion, in addition an ammonium or an organic amine group, and a=1 / 3, 1 / 2 or 1, depending on whether M is a monovalent, divalent or trivalent cation. The organic amine group used is preferably a substituted ammonium group derived from a primary, secondary or tertiary C 1-20 Alkylamine, C 1-20 Alkanolamine, C 5-8 Cycloalkylamines and C 6-14 Arylamines. Examples of amines that come into consideration are methylamine, dimethylamine, trimethylamine, ethanolamine, diethanolamine, triethanolamine, methyldiethanolamine, cyclohexylamine, dicyclohexylamine, aniline, diphenylamine in protonated (ammonium) form.
[0047] In a particularly preferred embodiment, the substituents in the structural unit (Va) have the following meanings: 3 and R 4 are independently hydrogen, an aliphatic hydrocarbon group having 1 to 10 carbon atoms,
[0048] R 5 It is H, -COOM a ,
[0049] M is hydrogen, a monovalent, divalent or trivalent metal ion, an ammonium ion or an organic amine group
[0050] a is 1 / 3, 1 / 2 or 1.
[0051] In another preferred embodiment, the water-soluble polymer is a copolymer comprising structural unit (Vb)
[0052]
[0053] R 6 , R 7 and R 8 are independently hydrogen, an aliphatic hydrocarbon group having 1 to 20 carbon atoms, an alicyclic hydrocarbon group having 5 to 8 carbon atoms or an optionally substituted aryl group having 6 to 14 carbon atoms, and
[0054] U, k, X, Alk, n and W have the above-mentioned meanings.
[0055] In a particularly preferred embodiment, the substituents in the structural unit (Vb) have the following meanings
[0056] R 6 , R 7 and R 8 are independently hydrogen, an aliphatic hydrocarbon group having 1 to 10 carbon atoms,
[0057] U is a chemical bond or an alkylene group having 1 to 8 carbon atoms,
[0058] X is oxygen,
[0059] k is 0 or 1,
[0060] n is an integer, based on the acid group-containing polymer, whose average value is in the range of 10 to 200,
[0061] Alk is a C2-C4 alkylene group, and in the group (Alk-O) n In, Alk can be the same or different,
[0062] W is hydrogen or C1-C6-alkyl.
[0063] Furthermore, in a specific embodiment, the present invention provides a sodium salt, potassium salt, ammonium salt and / or calcium salt of the copolymer, preferably a sodium salt and / or potassium salt.
[0064] In a preferred embodiment of the present invention, the copolymer of the present invention comprises at least one additional structural unit (additional monomer) different from the structural units of the general formulae (Va) and (Vb). Of course, the copolymer may also comprise a plurality of structural units different from the structural units of the general formulae (Va) and (Vb).
[0065] The copolymer may therefore be based on at least one further monomer, particularly preferably a monoethylenically unsaturated monomer.
[0066] Suitable additional monomers are C2-C 24 - Olefins, for example ethylene, propylene, 1-butene, 2-butene, isobutene, diisobutene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 1-octadecene.
[0067] Other suitable additional monomers include conjugated C4-C 10 - dienes, for example butadiene, isoprene or chloroprene.
[0068] The further monomer, in particular the monoethylenically unsaturated further monomer, can in particular be a monomer comprising at least one acid group, wherein the acid group can also be fully or partially neutralized. Here, the monomer can in particular be an alkali metal salt, an alkaline earth metal salt, an ammonium salt or a salt of an organic ammonium ion. The monomer can preferably be a monomer comprising at least one acid group, which is selected from the group consisting of a carboxylic acid, a sulfonic acid, a phosphoric acid or a phosphonic acid group.
[0069] Examples of suitable additional monomers having a carboxylic acid group include C3-C 12 Monoethylenically unsaturated mono- or dicarboxylic acids and their anhydrides or salts, for example acrylic acid, methacrylic acid, (meth)acrylic anhydride, crotonic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, mesaconic acid, citraconic acid or methylenemalonic acid and their ammonium salts or alkali metal salts. These acids can be used in fully or partially neutralized form.
[0070] Examples of suitable further monomers having phosphoric acid or phosphonic acid groups include monoethylenically unsaturated phosphonic acid esters or (poly)phosphates and their salts, for example esters of vinylphosphonic acid or hydroxyethyl, hydroxypropyl or hydroxybutyl (meth)acrylate with (poly)phosphoric acid and their alkali metal and ammonium salts, monovinyl phosphate, allylphosphonic acid, monoallyl phosphate, 3-butenylphosphonic acid, mono-3-butenyl phosphate, mono(4-vinyloxybutyl)phosphate, mono(2-hydroxy-3-vinyloxypropyl)phosphate, mono(1-phosphonooxymethyl-2-vinyloxyethyl)phosphate, mono(3-allyloxy-2-hydroxypropyl)phosphate, mono-2-(allyloxy-1-phosphonooxymethylethyl)phosphate, 2-hydroxy-4-vinyloxymethyl-1,3,2-dioxaphosphole, 2-hydroxy-4-allyloxymethyl-1,3,2-dioxaphosphole. It is also possible to use salts and / or esters of phosphoric acid and / or monomers comprising phosphonic acid groups, in particular the C1-C8 mono-, di- and optionally tri-alkyl esters.
[0071] Examples of suitable further monomers having sulfonic acid groups include monoethylenically unsaturated sulfonic acids and their salts, for example vinylsulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, 2-acrylamidomethyldodecylsulfonic acid, 2-(meth)acryloyloxyethanesulfonic acid, 3-(meth)acryloyloxypropanesulfonic acid, allyloxybenzenesulfonic acid, vinylbenzenesulfonic acid, vinyltoluenesulfonic acid, allylsulfonic acid, methylallylsulfonic acid and the corresponding ammonium salts and alkali metal salts thereof.
[0072] Suitable additional monomers are also esters, amides and imides of monoethylenically unsaturated mono- or dicarboxylic acids, in particular the above-mentioned monoethylenically unsaturated C3-C4 12 - carboxylic acids, especially C1-C 40 , preferably C1-C 22 , particularly preferably C2-C 12 The substituents may also carry additional heteroatoms. The dicarboxylic acids may also be present in the form of their monoesters or monoamides, for example as C1-C4 monoesters. Amides and imides may be present in N-monoalkylated form or optionally in N,N-dialkylated form.
[0073] In particular, the ester may be an ester of (meth)acrylic acid, in particular having an aliphatic or cycloaliphatic ester group, in particular a C1-C 22 , preferably C2-C 12 Examples of such compounds include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, 1-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, behenyl (meth)acrylate, cyclohexyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-propylheptyl (meth)acrylate, or citronellol (meth)acrylate.
[0074] The ester group may also contain heteroatoms, in particular O and / or N atoms. Examples of such esters include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, ethyl diglycol (meth)acrylate, hydroxypropyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, 2-phenylethyl (meth)acrylate, 3-phenylpropyl (meth)acrylate, ureido (meth)acrylate, acetoacetoxyethyl (meth)acrylate, hydroxyethylpyrrolidone (meth)acrylate, tert-butylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate. Examples of preferred (meth)acrylates include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate and hydroxybutyl (meth)acrylate.
[0075] The alcohol component in the (meth)acrylate may also be an alkoxylated alcohol. Here, particular mention should be made of alkoxylated C1-C 18 -alcohol, which contains 2 mol to 80 mol of ethylene oxide, propylene oxide, butylene oxide or a mixture thereof. Examples of such alkoxylation products include C 13 / C 15 Methyl polyethylene glycol (meth)acrylate or (meth)acrylate of oxo alcohol, or a mixture thereof.
[0076] Further examples of esters, amides or imides include monoethyl maleate, diethyl maleate, dimethyl maleate, N-substituted maleimides such as N-methylmaleimide, N-phenylmaleimide and N-cyclohexylmaleimide, acrylamide, methacrylamide, N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethylacrylamide, N-isopropyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, methyl)acrylamide, N-tert-butyl(meth)acrylamide, N-tert-octyl(meth)acrylamide, N-(1-methylundecyl)(meth)acrylamide, 10-acrylamidoundecanoic acid, N-cyclohexyl(meth)acrylamide, diacetoneacrylamide, dimethylaminoethyl(meth)acrylamide, dimethylaminopropyl(meth)acrylamide, N,N-dimethyl-N-(meth)acrylamidopropyl-N-(3-sulfopropyl)ammonium betaine, (meth)acryloylmorpholine.
[0077] The monomers carrying amino or imino groups can also be present in protonated form or in the form of their quaternized salts, for example by quaternization with methyl chloride, dimethyl sulfate or diethyl sulfate. The monomers can also react with propane sultone to form the corresponding betaines.
[0078] Likewise suitable are further monomers which contain N-vinyl groups, for example N-vinylpyrrolidone, N-vinylcaprolactam, N-vinyl-N-methylacetamide, N-vinylimidazole, 2-methyl-1-vinylimidazole, quaternized N-vinylimidazole derivatives, for example 1-vinyl-3-methylimidazolium chloride or methylsulfate, N-vinyl-1,2,4-triazole, N-vinylcarbazole, N-vinylformamide, 2-methyl-1-vinylimidazole.
[0079] Suitable additional monomers are also vinyl alcohol and C1-C2 monocarboxylic acids. 24 Esters, for example vinyl formate, vinyl acetate, vinyl propionate, vinyl n-butyrate, vinyl laurate, vinyl stearate, or vinyl esters of Koch acids, for example vinyl esters of 2,2-dimethylpropionic acid, 2,2-dimethylbutyric acid, 2,2-dimethylpentanoic acid, 2-ethyl-2-methylbutyric acid, neononanoic acid, neodecanoic acid.
[0080] Vinyl ethers or allyl ethers, such as methyl vinyl ether, ethyl vinyl ether, propyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, 2-ethylhexyl vinyl ether, vinyl cyclohexyl ether, vinyl 4-hydroxybutyl ether, decyl vinyl ether, dodecyl vinyl ether, octadecyl vinyl ether, hydroxybutyl vinyl ether, 2-(diethylamino)ethyl vinyl ether, 2-(di-n-butylamino)ethyl vinyl ether or methyl diglycol vinyl ether, and the corresponding allyl compounds are also suitable.
[0081] Further suitable monomers are unsaturated alcohols such as 3-butene-1-ol, 2-butene-1-ol, allyl alcohol, isoprenol, isoprenol, methylallyl alcohol.
[0082] Suitable further monomers are likewise N-allyl compounds, for example diallylamine, N,N-dimethyl-N,N-diallylammonium chloride.
[0083] Suitable further monomers are also α,β-monoethylenically unsaturated nitriles having 3 to 10 carbon atoms, for example acrylonitrile, methacrylonitrile, fumaronitrile, maleonitrile.
[0084] Suitable further monomers are also vinyl aromatic monomers such as styrene, vinyl toluene or α-methylstyrene. Other styrene derivatives conform to the general formula VI
[0085]
[0086] Where R 11 and R 21 is each hydrogen or C1-C8-alkyl, and n is 0, 1, 2 or 3. The aromatic rings may additionally carry heteroatoms, for example 2- and 4-vinylpyridine.
[0087] Suitable additional monomers are also halogenated olefins, for example vinyl chloride, vinylidene chloride, trifluoroethylene, tetrafluoroethylene, and also acrolein, methacrolein.
[0088] The additional monomers may also be monomers with a crosslinking effect. Examples of suitable crosslinking additional monomers include molecules with multiple ethylenically unsaturated groups, for example di(meth)acrylates, such as ethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate or hexanediol di(meth)acrylate, or poly(meth)acrylates, such as trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, or di(meth)acrylates of oligoalkylene glycols or polyalkylene glycols, such as diethylene glycol, triethylene glycol or tetraethylene glycol or dipropylene glycol, tripropylene glycol or tetrapropylene glycol di(meth)acrylate. Other examples include divinylbenzene, divinylethylene urea, vinyl (meth)acrylate, allyl (meth)acrylate, isoprene (meth)acrylate, isoprenyl (meth)acrylate, dihydrodicyclopentadiene acrylate, dicyclopentadiene (meth)acrylate or butanediol divinyl ether. Diallyl ethers and oligomeric allyl ethers or vinyl ethers of polyhydroxy compounds, such as ethylene glycol divinyl ether, butanediol divinyl ether, 1,4-cyclohexanedimethanol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, pentaerythritol triallyl or tetraallyl ether are also suitable. Oligomeric allylamines, such as triallylamine or tetraallylammonium chloride are also suitable. Diallyl esters and oligomeric allyl esters of polycarboxylic acids, such as diallyl phthalate, diallyl maleate, triallyl trimellitate, dicarboxylic acids such as divinyl esters of succinic acid and adipic acid are also suitable. Di(methyl)acrylamide, tri(methyl)acrylamide or oligomeric (methyl)acrylamide, such as N,N'-methylenebis(methyl)acrylamide are also suitable. The content of crosslinking monomers is generally 0 to 20 mol %, preferably 0.1 to 10 mol %, particularly preferably 0.2 to 5 mol %, based on the total amount of all monomers. The polymers according to the invention preferably do not contain any crosslinking monomers.
[0089] Examples of preferred monoethylenically unsaturated additional monomers include styrene, butadiene, methyl (meth)acrylate, ethyl acrylate, dibutyl maleate, methyl α-cyanoacrylate, acrylonitrile, acrylic acid, methacrylic acid, maleic acid / anhydride, itaconic acid, vinylphosphonic acid, N-vinylpyrrolidone, N,N-dimethyl-N,N-diallylammonium chloride, acrylamide, vinylimidazole, vinyl acetate, allylsulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, particularly preferably acrylic acid, methacrylic acid, methyl (meth)acrylate, maleic acid / anhydride, (iso)isoprenyl alkoxylates, (meth)allyl alkoxylates or hydroxybutyl vinyl ether alkoxylates. Very particular preference is given to acrylic acid, methacrylic acid, (meth)acrylates, maleic acid / anhydride, (iso)isoprenyl alkoxylates, (meth)allyl alkoxylates or hydroxybutyl vinyl ether alkoxylates.
[0090] In another preferred embodiment of the copolymer according to the invention, acrylic acid is contained in the polymer as at least one additional structural unit different from the structural units of the general formulae (Va) and (Vb). In this case, it is particularly preferred that no additional structural units are contained in addition to the structural units of the general formulae (Va) and (Vb) and the structural units based on acrylic acid.
[0091] In another preferred embodiment of the copolymer according to the invention, methacrylic acid is contained in the polymer as at least one additional structural unit different from the structural units of the general formulae (Va) and (Vb). In this case, it is particularly preferred that no additional structural units are contained in addition to the structural units of the general formulae (Va) and (Vb) and the structural units based on methacrylic acid.
[0092] In another preferred embodiment of the copolymer according to the invention, maleic acid / anhydride is contained in the polymer as at least one additional structural unit different from the structural units of the general formulae (Va) and (Vb). In this case, it is particularly preferred that, in addition to the structural units of the general formulae (Va) and (Vb) and based on maleic acid / anhydride, no additional structural units are contained.
[0093] Due to the way they are prepared, the copolymers according to the invention may also comprise small amounts of initiators or chain transfer agents.
[0094] In a further preferred embodiment of the copolymer according to the invention, apart from (Va), (Vb) and the structural units based on acrylic acid and methacrylic acid or acrylic acid and maleic acid / anhydride or methacrylic acid and maleic acid / anhydride, no further structural units are contained.
[0095] In a further preferred embodiment of the copolymer according to the invention, apart from (Va), (Vb) and the structural units based on acrylic acid, methacrylic acid and maleic acid / anhydride, no further structural units are contained.
[0096] In a preferred embodiment, the copolymer according to the invention comprises 5 to 99% by weight of unsaturated compounds of the general formula (Va) and 5 to 99% by weight of unsaturated compounds of the general formula (Vb), in each case based on the total amount of monomers in the polymer. Preferably, the copolymer according to the invention comprises 10 to 90% by weight of unsaturated compounds of the general formula (Va) and 10 to 90% by weight of unsaturated compounds of the general formula (Vb), in each case based on the total amount of monomers in the polymer.
[0097] The average molecular weight M of the copolymers of the invention determined by gel permeation chromatography (GPC) is w Preferably, it is 2000 g / mol to 200 000 g / mol, more preferably 5 000 g / mol to 80 000 g / mol, and very preferably 8000 g / mol to 70 000 g / mol. The average molar mass and conversion of the polymer are analyzed by size extrusion chromatography (column combination: OH-Pak SB-G, OH-Pak SB 804HQ and OH-Pak SB 802.5HQ, purchased from Shodex, Japan; eluent: 80% by volume of HCO2NH4 aqueous solution (0.05 mol / l) and 20% by volume of acetonitrile; injection volume: 100 μl; flow rate 0.5 ml / min). Calibration is performed with linear polyethylene glycol standards to determine the average molar mass. As a measure of the conversion, the peak of the copolymer is standardized to a relative height of 1, and the height of the peak of the unreacted macromonomer / PEG-containing oligomer is used as a measure of the residual monomer content.
[0098] In a particularly preferred embodiment, the water-soluble polymer is a polycondensation product comprising
[0099] (II) structural units containing aromatic or heteroaromatic and polyether groups,
[0100] (III) A structural unit containing a hydroxamic acid group or a salt thereof and an aromatic or heteroaromatic moiety.
[0101] The structural units (II) and (III) are preferably represented by the following general formula:
[0102] (II)AU-(C(O)) k -X-(AlkO) n -W
[0103] in
[0104] A are identical or different and are represented by a substituted or unsubstituted aromatic or heteroaromatic compound having 5 to 10 carbon atoms in the aromatic system,
[0105] U, k, X, Alk, n and W have the meanings as described for structural unit (I),
[0106] (III)
[0107]
[0108] in
[0109] D is identical or different and is represented by a substituted or unsubstituted aromatic or heteroaromatic compound having 5 to 10 carbon atoms in the aromatic system, wherein
[0110] E is a chemical bond
[0111] or -(C(O)) k -X-(AlkO) n -Z-,
[0112] in
[0113] X is oxygen or the group NR 9 , preferably X is oxygen,
[0114] k is 0 or 1, preferably k is 0
[0115] n is an integer, based on the acid group-containing polymer, and its average value is from 0 to 100, preferably from 0 to 25, most preferably from 0 to 5,
[0116] Alk is a C2-C4 alkylene group, and in the group (Alk-O) n In, Alk can be the same or different,
[0117] R 9 is H, C1-C4 alkyl or benzyl
[0118] Z is a C1-C3 alkylene group, preferably Z is a C1 or C2 alkylene group.
[0119] The polycondensation product preferably contains an additional structural unit (IV) represented by the formula
[0120] (IV)
[0121]
[0122] in
[0123] Each Y is independently a structural unit (II), a structural unit (III) or an additional component of a polycondensation product, and each R 5 and each R 6is independently H, CH3, COOH or a substituted or unsubstituted aromatic or heteroaromatic compound having 5 to 10 carbon atoms.
[0124] In a particularly preferred embodiment, R 5 and R 6 Indicated by H.
[0125] The molar ratio of the structural units (II), (III) and (IV) in the polycondensation product of the invention can vary within a wide range. It has proven useful that the molar ratio of the structural units [(II) + (III)]: (IV) is 1:0.8 to 3, preferably 1:0.9 to 2, more preferably 1:0.95 to 1.2.
[0126] The molar ratio of structural units (II):(III) is generally 1:15 to 15:1, preferably 1:7 to 5:1, more preferably 1:5 to 3:1.
[0127] The groups A and D in the structural units (II) and (III) of the polycondensation product are usually represented by phenyl, 2-hydroxyphenyl, 3-hydroxyphenyl, 4-hydroxyphenyl, 2-methoxyphenyl, 3-methoxyphenyl, 4-methoxyphenyl, naphthyl, 2-hydroxynaphthyl, 4-hydroxynaphthyl, 2-methoxynaphthyl, 4-methoxynaphthyl, preferably phenyl, and A and D can be selected independently of each other and can also each be composed of a mixture of the compounds. The group X is preferably represented by O. The group E is preferably represented by a chemical bond.
[0128] In structural unit (II), n is preferably represented by an integer of 5 to 280, more preferably 10 to 160, and more preferably 12 to 120. Here, the group whose length is defined by n can be composed of a single structural group, but a mixture of different structural groups is also useful. In addition, the groups of structural unit (II) can each have the same chain length, wherein n is represented by a number. However, in general, in each case, it is useful to have a mixture with different chain lengths so that the groups of the structural units in the polycondensation product have different n values.
[0129] Furthermore, in a specific embodiment, the present invention provides a sodium salt, potassium salt, ammonium salt and / or calcium salt of the polycondensation product, preferably a sodium salt and / or potassium salt.
[0130] The polycondensation product of the present invention generally has a weight average molecular weight of 3000 g / mol to 150000 g / mol, preferably 5000 g / mol to 100 000 g / mol, and more preferably 10 000 g / mol to 75 000 g / mol, as determined by gel permeation chromatography (GPC). The average molar mass and conversion of the polymer are analyzed by size extrusion chromatography (column combination: OH-Pak SB-G, OH-Pak SB 804HQ and OH-Pak SB 802.5HQ, purchased from Shodex, Japan; eluent: 80% by volume of HCO2NH4 aqueous solution (0.05 mol / l) and 20% by volume of acetonitrile; injection volume: 100 μl; flow rate 0.5 ml / min). Calibration is performed with linear polyethylene glycol standards to determine the average molar mass. As a measure of conversion, the copolymer peak was normalized to a relative height of 1, and the height of the unreacted macromer / PEG-containing oligomer peak was used as a measure of the residual monomer content.
[0131] In a preferred embodiment, the polymer of the present invention comprises at least one of carboxyl, phosphonyl, sulfinyl, sulfo, sulfonamido, sulfooxy, sulfoalkoxy, sulfinylalkoxy and phosphonooxy groups. Particularly preferred are carboxyl and phosphonooxy groups.
[0132] In a preferred embodiment of the invention, the average ratio of the number of moles of hydroxamic acid groups or salts thereof of the polymer to the total molar mass of the polymer is from 1 / 200 mol / (g / mol) to 1 / 2000 mol / (g / mol), wherein cations associated with the comb polymer, including protons, are not taken into account in calculating the total molar mass of the polymer.
[0133] In a particularly preferred embodiment, the composition of the invention is in powder form. The average particle size of the powder of the invention is preferably less than 400 μm, more preferably less than 100 μm, and more specifically between 1 μm and 250 μm, more preferably between 1 μm and 75 μm, as measured by laser granulometry. In the present patent application, the term "average particle size" corresponds to the median value of the particle volume distribution, i.e. the D50 value.
[0134] The present invention also provides a method for preparing a water-soluble polymer comprising a hydroxamic acid group or a salt thereof according to the present invention, wherein the water-soluble polymer comprises
[0135] a) a main chain, which consists of at least
[0136] A carbon chain of 16 carbon atoms, and
[0137] b) polyether side chains, and
[0138] c) a carboxylate attached to the backbone,
[0139] The water-soluble polymer is reacted with hydroxylamine in an aqueous medium.
[0140] In a preferred embodiment, the process is carried out at a pH between 11.5 and 13.5.
[0141] In another preferred embodiment, the process is carried out at a temperature between 10° C. and 50° C. Preferably, the hydroxylamine source is hydroxylamine hydrochloride or hydroxylammonium sulfate.
[0142] Furthermore, in a specific embodiment, the present invention provides an inorganic particle composition comprising the water-soluble polymer according to the present invention. In a particularly preferred embodiment, the composition comprises an inorganic binder or an inorganic pigment.
[0143] The inorganic binder is preferably at least one from the group consisting of a portland cement based cement, white cement, calcium aluminate cement, calcium sulphoaluminate cement, n-hydrated calcium sulphate and latent hydraulic and / or pozzolanic binders.
[0144] Binders based on calcium sulfate can exist in different hydrate states. Preferred binders according to the invention are α-calcium sulfate hemihydrate, β-calcium sulfate hemihydrate and anhydrite without crystallization water, or mixtures of said binders. Particularly preferred is β-calcium sulfate hemihydrate, and especially preferred is β-calcium sulfate hemihydrate containing anhydrite, more particularly anhydrite III. Anhydrite dust (finely ground anhydrite) can also be used, which reacts relatively slowly and produces only partial solidification.
[0145] In a preferred embodiment of the present invention, the calcium sulfate-based binder comprises clay. The clay content is generally in the range of 0.0001 wt % to 15 wt %, preferably 0.01 wt % to 10 wt %, based on the weight of the gypsum. Another aspect of the present invention is a gypsum-containing composition as described above, wherein the clay is a swellable clay, including but not limited to clays such as bentonite.
[0146] In a specific embodiment, the composition comprising an inorganic binder preferably contains at least 30% by weight, particularly preferably at least 50% by weight, most preferably at least 70% by weight of a binder based on calcium sulfate, more particularly calcium sulfate β-hemihydrate, based on the total weight of the mineral binder. The composition comprising an inorganic binder may include other mineral binders, examples being hydraulic substances such as cement, more particularly Portland cement or fused alumina cement, and mixtures thereof with fly ash, silica dust, slag, slag sand and limestone or quicklime, respectively. The mixture may also contain other additives, such as fibers, and ingredients that are usually additives, such as other dispersants, for example lignin sulfonates, sulfonated naphthalene-formaldehyde condensates, sulfonated melamine-formaldehyde condensates or polycarboxylate ethers (PCEs), accelerators, retarders, starches, sugars, silicones, shrinkage reducers, defoamers or foaming agents.
[0147] In another preferred embodiment, the composition comprising an inorganic binder is a dry-mix mortar. Due to continuous efforts to achieve extensive rationalization and improve product quality, mortars for various purposes in the construction industry are now almost no longer mixed from starting materials on the construction site. Today, this function is mainly completed by the building materials industry in the factory, and the ready-to-use mixture is provided in the form of so-called factory dry-mix mortar. According to DIN 18557, the finished mixture that can be used on site only by adding water and mixing is called factory mortar, more specifically factory dry-mix mortar. This mortar system can meet any of a variety of physical construction goals. According to the purpose of existence, the binder (which may include, for example, cement and / or lime and / or calcium sulfate) is mixed with other additives and / or admixtures so that the factory dry-mix mortar is adapted to a specific application. The additives and admixtures considered may include, for example, shrinkage reducers, expansion agents, promoters, retarders, dispersants, thickeners, defoamers, air entraining agents and corrosion inhibitors.
[0148] The factory dry-mixed mortar of the present invention may specifically include masonry mortar, plastering mortar, mortar for thermal insulation composite systems, repair plastering, joint mortar, tile adhesive, thin-layer mortar, leveling mortar, casting mortar, injection mortar, filling compound, mortar or lining mortar (for example for drinking water pipes).
[0149] Also included are factory mortars produced on the building site, which are supplied not only with water but also with further components, in particular liquid and / or powdered additives, and / or with aggregates (two-component systems).
[0150] Compositions comprising the inorganic binder of the invention may also specifically comprise a binder mixture as its binder. In the context of the present invention, this is understood to be a mixture of at least two binders selected from the group consisting of cement, pozzolanic and / or latent hydraulic binders, white cement, special cement, calcium aluminate cement, calcium sulfoaluminate cement and various hydrated and anhydrous calcium sulfates. These mixtures may then optionally contain further additives.
[0151] In another preferred embodiment, the inorganic particle composition of the present invention comprises an inorganic pigment. Preferably, the inorganic pigment is selected from the group consisting of titanium dioxide, kaolin, clay, talc, calcium hydroxide, ultrafine precipitated calcium carbonate, ground calcium carbonate, black pigments such as iron (III) oxide or titanium (III) oxide or manganese oxide. In a preferred embodiment, the pigment is present in the form of a pigment slurry.
[0152] The present invention is particularly applicable to these inorganic pigment slurries which tend to have particularly fine particle sizes, especially when these inorganic pigment slurries appropriately have a pH greater than 7. The present invention solves the problem that it may be difficult to obtain a balance of properties when producing these particular inorganic pigment slurries. The present invention can be suitable for forming stable and effective aqueous slurries of such inorganic pigments.
[0153] In a specific embodiment, the inorganic pigment slurry comprises a water-soluble polymer according to the present invention in a dosage of up to 3% by weight, based on the total dry weight of the pigment particles. However, in general, the optimal dosage of the polymer is usually below this level. The exact dosage can vary depending on the specific inorganic pigment, the average particle size of the pigment and the desired solid content of its slurry.
[0154] In a preferred embodiment, the inorganic particle composition according to the present invention comprises 0.005 to 3 wt%, preferably 0.03 to 2 wt%, most preferably 0.07 to 1 wt% of water-soluble polymer, based on the total dry weight of the inorganic particles.
[0155] Finally, the present invention also comprises the use of the water-soluble polymer according to the invention as a dispersant in an inorganic particle composition. Preferably, the water-soluble polymer according to the invention is used to control the fluidity of an aqueous chemical building suspension, which is preferably based on an inorganic binder, in particular comprising at least one of the following inorganic binders: n-hydrated calcium sulfate, hydraulic binder, latent hydraulic binder.
[0156] In another aspect, the water-soluble polymer according to the present invention is used for
[0157] Aqueous slurries of stabilized inorganic pigments.
[0158] In a specific embodiment, the present invention relates to the use of a water-soluble polymer according to the invention for producing a shaped gypsum body. The term "shaped body" refers to any cured product having a three-dimensional extent. The curing of the shaped body is completed by drying in an oven or in air. The shaped body of the present invention may be a movable object, such as a gypsum board or a sculpture. Alternatively, the shaped body of the present invention may be a filler or a coating, for example a gypsum render, a floor covering or a leveling layer, or any product formed upon spreading and curing of a filling compound, for example a filling of a cavity or a joint.
[0159] The invention particularly preferably envisages a shaped gypsum body in the form of a gypsum plasterboard comprising the dispersant according to the invention. The invention also comprises a method for producing a gypsum plasterboard using the dispersant according to the invention. In the production of gypsum building boards, more particularly gypsum plasterboards, the speed of the setting process is of crucial importance. Currently, more than 8 billion m3 of gypsum plasterboards are produced worldwide each year. 2 . The production of gypsum plasterboards has a long history. It is described, for example, in US Pat. No. 4,009,062. The settable gypsum slurry used consists of calcium sulfate hemihydrate and water, is usually produced in a high-speed rotating flow mixer, is applied continuously to a cardboard web and covered with a second cardboard sheet. The two cardboard webs are called front board and back board. The board line then moves along a so-called setting belt, and at the end of the setting belt, the settable calcium sulfate phase is almost completely converted into calcium sulfate dihydrate. After this hardening, the web is divided into boards and the water still present in the boards is removed in a heated multi-stage dryer.
[0160] This type of gypsum plasterboard is used to a large extent in interior finishing of ceilings and walls.
[0161] In order to meet the growing demand and to minimize production costs, efforts are constantly being made to improve production processes. Modern plants for manufacturing gypsum building boards can reach production speeds of up to 180 meters per minute. Only by using efficient accelerators can the plant's production capacity be utilized to the maximum. Here, the setting time of the calcium sulfate hemihydrate determines the time until the gypsum plasterboard can be cut, which in turn determines the length and speed of the conveyor belt and, therefore, the production rate. In addition, hydration must be completed before the board is exposed to high temperatures in the dryer. Otherwise, the strength potential of the binder is not fully developed and there is a risk of volume expansion due to the ingress of water after hydration.
[0162] Therefore, minimizing the retarding of the setting process by using a dispersant has considerable economic benefits. Therefore, the present invention also includes a method for producing gypsum plasterboard using the water-soluble polymer according to the present invention. Here, the water-soluble polymer according to the present invention can be used in the same way as the currently known dispersants, so that no further changes to the production operation are required.
[0163] In another preferred embodiment, the shaped gypsum body of the present invention can be a self-leveling screed containing calcium sulfate. Also included is a method for producing a self-leveling screed containing calcium sulfate using the dispersant of the present invention.
[0164] The following examples illustrate the advantages of the present invention. Example
[0165] Polymer synthesis
[0166] Polymer 1
[0167] 267 g of water and 330.9 g of molten vinyl-PEG 3000 (solution A) were charged into a glass reactor vessel equipped with multiple necks, a mechanical stirrer, a pH meter and a metering device (e.g., a syringe pump). The temperature in the reactor was adjusted to 13° C. and the pH was adjusted to about 7 by adding 3 g of a 25% sulfuric acid solution.
[0168] A portion (20.5 g) of a pre-prepared second solution (solution B) consisting of 152.11 g of water and 52.82 g of hydroxyethyl acrylate (HEA, 98.5%) was added dropwise to the reactor vessel over 10 minutes under moderate stirring. The pH of the resulting solution in the reactor was measured to be 6.8. 2.9 g of 3-mercaptopropionic acid (3-MPA) was added to the remaining solution B. Just before initiating polymerization, an additional 0.52 g of 3-MPA was added to the reactor. A third solution (solution C) containing 1.5 g of sodium hydroxymethanesulfinate dihydrate in 48.5 g of water was prepared. Polymerization was initiated by adding a solution of 21 mg FeSO4×7H2O and 1.34 g H2O2 (30%) dissolved in several milliliters of water to the reaction vessel. At the same time, solutions B and C were metered into the polymerization vessel. Solution B was metered in over 30 minutes using different addition rates as described in the following table. Solution C was metered in at a constant rate of 1.54 g / h over 30 minutes and subsequently at a higher rate of 50 g / h over a further 10 minutes. During the 30-minute metering of solution B, the pH in the reactor was maintained at 6.8 by adding a 20% aqueous NaOH solution. The pH of the polymer solution after addition of solution C was 7.1, and 0.2 g of 25% sulfuric acid was added to adjust the pH to 7. An aqueous solution of a polyether-polyester copolymer was obtained with a yield of 91%, a weight-average molecular weight of 37 kDa (GPC; verses PEO / PEG standards) and a solids content of 46.8%. The polymer solution was concentrated to 48.4% by a rotary evaporator.
[0169] Polymer 2
[0170] 200 g of polymer solution 1 was placed in a double-walled reaction vessel (1000 mL four-necked flask) equipped with a reflux condenser, agitator, a thermometer, a pH meter and a dropping funnel. While stirring, 96.8 g of a 50% sodium hydroxide solution was added dropwise thereto. After stirring for 30 minutes, a pH of 13.5 was obtained. The reaction solution was stirred at room temperature for 24 hours. After neutralizing the reaction mixture with a corresponding amount of sulfuric acid solution (25%), a pH of 7.2 was obtained. Dialysis (cellulose ester membrane tube; MWCO 500-1000 Da) was used to purify in 30 L of water (changing water) for 24 hours. The polymer solution was concentrated using a rotary evaporator. The resulting product was a solid content of 31.8 wt % and a molecular weight of M W A solution of a polymer of 37 kDa (GPC; reference PEO / PEG-standard).
[0171] Polymer 3
[0172] 200 g of polymer solution 1 was placed in a double-walled reaction vessel (1000 mL four-necked flask) equipped with a reflux condenser, a stirrer, a thermometer, a pH meter and a dropping funnel, and 28.06 g of hydroxylamine hydrochloride (99.9%) in 50 g of water was added dropwise while stirring. A pH of 4.8 was obtained, and the solution was stirred at room temperature for 30 minutes. While stirring, 96.8 g of a cold sodium hydroxide solution (50%) at 5° C. to 10° C. was added dropwise over 20 minutes. The reaction mixture reached a temperature of ~30° C. and a pH of 13.1. After stirring for 1 hour, 8.0 g of a cold sodium hydroxide solution (50%) at 5° C. to 10° C. was added dropwise. After stirring overnight, the pH was adjusted to pH 13 by using a corresponding amount of sodium hydroxide solution (50%) added dropwise under stirring. After stirring for 1 hour, the reaction mixture was neutralized by adding sulfuric acid solution (25%) until the pH was 7.1. The polymer was purified using dialysis (cellulose ester membrane tubing; MWCO 500-1000 Da) in 10 L of water (water change) for 24 hours. The polymer solution was concentrated using a rotary evaporator. The resulting product was a polymer solution with a solids content of 37.0%. The proportions of carbon, hydrogen and nitrogen in the polymer were determined by elemental analysis (vario EL CUBE from Elementar, combustion temperature 950° C.) and compared with theoretical values. Thereafter, the ester of polymer 1 was converted into 33% of hydroxamic acid and 67% of carboxylic acid.
[0173] Polymer 4
[0174] 138 g of water and 182 g of molten vinyl-PEG 1100 (Solution A) were charged into a glass reactor vessel equipped with multiple necks, a mechanical stirrer, a pH meter and a metering device (e.g., a syringe pump). The temperature in the reactor was adjusted to 12° C. and the pH was adjusted to about 7 by adding 4 g of a 25% sulfuric acid solution.
[0175] A portion (59.63 g) of a pre-prepared second solution (solution B) consisting of 228.17 g of water and 79.22 g of hydroxyethyl acrylate (HEA, 98.5%) was added dropwise to the reactor vessel over 10 minutes while stirring moderately. The pH of the resulting solution in the reactor was measured to be 6.5. 2.28 g of 3-mercaptopropionic acid (3-MPA) was added to the remaining solution B. Just before initiating polymerization, an additional 0.76 g of 3-MPA was added to the reactor. A third solution (solution C) containing 1.5 g of sodium hydroxymethanesulfinate dihydrate in 48.5 g of water was prepared. Polymerization was initiated by adding a solution of 31 mg FeSO4×7H2O and 2.01 g H2O2 (30%) in several milliliters of water to the reaction vessel. At the same time, solutions B and C were metered into the polymerization vessel. Solution B was metered in over 30 minutes. Solution C was metered in at a constant rate of 4.5 g / h over 30 minutes and subsequently at a higher rate of 75 g / h over a further 6 minutes. During the 30-minute metering of solution B, the pH in the reactor was maintained at 6.5 by adding a 20% aqueous NaOH solution. The pH of the polymer solution after addition of solution C was 7.1, and 0.24 g of a 25% sulfuric acid solution was added to adjust the pH to 7. An aqueous solution of a polyether-polyester copolymer was obtained with a yield of 97.7% and a weight-average molecular weight M W The polymer solution was -37 kDa (GPC; compared to PEO / PEG-standards) and the solids content was 38.9%. The polymer solution was concentrated to 42.8% by rotary evaporator.
[0176] Polymer 5
[0177] In a similar procedure to the synthesis of polymer 3, an aliquot (40.0 g) of polymer 4 solution was mixed with 4.9 g of 48% sodium hydroxide solution overnight. After neutralization and purification via dialysis (as described for polymer 2), the resulting polymer solution had a solids content of 18.0% and a molecular weight M of ˜37 kDa. W (GPC; reference PEO / PEG-standard).
[0178] Polymer 6
[0179] In a procedure similar to the synthesis of polymer 3, an aliquot (70.1 g) of polymer 4 solution was mixed with 10.64 g of hydroxylamine hydrochloride (98%) in 40 g of water. During the overnight reaction, the pH was kept constant at ~13 by adding sodium hydroxide solution (18%). After neutralization and purification via dialysis (as described for polymer 3), the resulting polymer solution had a solid content of 8% and a molecular weight M of ~37 kDa.W (GPC; comparison with PEO / PEG standards). The proportions of carbon, hydrogen and nitrogen in the polymer were determined by elemental analysis (vario EL CUBE from Elementar, combustion temperature 950° C.) and compared with the theoretical values. Thereafter, the esters of polymer 4 were converted to 52% of the hydroxamic acid and 48% of the carboxylic acid.
[0180] Polymer 7
[0181] Synthesis of ring-opened maleic anhydride and hydroxamic acid = MSA-hydroxamic acid:
[0182] In a reactor (250 mL four-necked flask) equipped with a reflux condenser, agitator, a thermometer, a pH meter, a dropping funnel, an Almemo data logger, a solution of 10.21 g of hydroxylammonium chloride (98%) in 50 mL of water was stirred. At 25 ° C, while stirring, a 20% sodium hydroxide solution was added dropwise until a pH of 7 to 8 was reached. Then, 14.26 g of maleic anhydride (99%) was added under stirring within 1 hour, and the reaction temperature was maintained at 25 ° C by cooling. During this period, the pH was kept constant between 7 and 8 by subsequent metering of sodium hydroxide solution. After stirring for 30 minutes, the reaction mixture was evaporated to dryness. The pale yellow residue was mixed with toluene and evaporated to dryness. A brown solid substance with a purity of 70% determined by 1H-NMR was obtained. These by-products are produced by competing reactions (Michael addition).
[0183] A reactor (100 mL three-necked flask) equipped with a reflux condenser, a stirrer, a thermometer, a pH meter, a dropping funnel, an Almemo data recorder, and two feeding devices was charged with 20 g of water. While stirring, 17.6 g of molten VOBPEG 1100 was added thereto.
[0184] Subsequently, in a separate feed container, 0.24 g of Rongalit C were mixed with 11.76 g of water (solution 1). In parallel, a solution of 4.56 g of MSA-hydroxamic acid and 10.65 g of water was prepared (solution 2).
[0185] After the temperature was raised to 25° C., 7.6 g of solution 2, 0.04 g of 3-mercaptopropionic acid and 0.015 g of Fe2(SO4)3*7H2O were added to the VOBPEG solution. Then, 0.07 g of 3-mercaptopropionic acid was added to the remaining solution 2.
[0186] After the pH was adjusted to 5.0 by adding the corresponding amount of 10% sulfuric acid solution, 0.5 g of a 50% strength aqueous H2O2 solution was added. Then, the addition of solutions 1 and 2 was started, while the pH was kept constant between 4.8 and 5.2. Solution 1 was added at a metering rate of 2.9 mL / h and solution 2 was added at a rate of 27 mL / h. After the addition of solution 2 was completed, solution 1 was continued to be added until the solution was free of peroxide. The pH of the resulting polymer solution was adjusted to 6.5 with a 20% strength aqueous sodium hydroxide solution. The resulting polymer solution had a solid content of 33.0% and a molecular weight M of ~5 kDa. W (GPC; reference PEO / PEG-standard).
[0187] Polymer 8
[0188] 464 g of water were placed in a 1000 mL double-walled reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, a pH meter, a dropping funnel, an Almemo data logger and several feed devices. While stirring, 377 g of molten VOBPEG 3000 were added thereto. After the solution was thermostated to 15° C., 0.04 g of Fe2(SO4)3*7H2O, 3.3 g of Rongalit C, 4.5 g of 3-mercaptopropionic acid and 133.4 g of 2-hydroxyethyl acrylate (98% ig) were added. The cooling device was removed and 1.3 g of a 50% strength H2O2 aqueous solution was added thereto. After the addition, the reaction mixture reached a temperature of 30° C. within 2 minutes and stirring was continued for 30 minutes. The resulting product had a solid content of 51.6% by weight and a molecular weight of M W A polymer solution of -28 kDa (GPC; reference PEO / PEG-standard).
[0189] Polymer 9
[0190] In a similar procedure to the synthesis of polymer 2, an aliquot (550 g) of polymer 8 solution was mixed with 72.7 g of 31% sodium hydroxide solution overnight. After neutralization and purification via dialysis (as described for polymer 2), the resulting polymer solution had a solids content of 31.8% and a molecular weight M of ˜28.0 kDa. W (GPC; reference PEO / PEG-standard).
[0191] Polymer 10
[0192] In a procedure similar to the synthesis of polymer 3, an aliquot of polymer 8 solution (530.0 g) was mixed with 12.7 g of hydroxylamine hydrochloride (99.9%) in 50 g of water. During the overnight reaction, the pH was kept constant at ˜13 by adding sodium hydroxide solution (50%). After neutralization with sulfuric acid (25%) and purification via dialysis (as described for polymer 3), the resulting polymer solution had a solid content of 37.0% and a molecular weight M of ˜28.2 kDa. W (GPC; comparison with PEO / PEG standards). The proportions of carbon, hydrogen and nitrogen in the polymer were determined by elemental analysis (vario EL CUBE from Elementar, combustion temperature 950° C.) and compared with the theoretical values. Thereafter, the ester of polymer 8 was converted into 30.5% of the hydroxamic acid and 69.5% of the carboxylic acid.
[0193] Two binder formulations were used to demonstrate the fluidization ability and clay firmness of the compositions of the present invention:
[0194] Stucco A, pure clay-free β-hemihydrate from FGD, and clay-containing stucco B. Stucco B was obtained by loading the clay-free FGD stucco with clay by replacing 0.07 mass % of stucco with 0.70 % of bentonite Na-form.
[0195] Plast Retard L is a commercial product of Sicit 2000. Bentonite Na-type (10232802) is the clay mineral used.
[0196] Slump test
[0197] The flow rate is determined after 60 seconds. After adding the powder components to the liquid, the plaster must soak for 15 seconds. The slurry is then mixed with a Hobart stirrer for 30 seconds. After a total time of 45 seconds, the ASTM ring is filled with plaster slurry up to the top edge and lifted after 60 seconds. Finally, the cake diameter is measured with a caliper in two perpendicular axes.
[0198] Hardening time
[0199] The initial setting was determined by the so-called knife cut method (similar to DIN EN 13279-2).
[0200] Slurry preparation
[0201] Reference Example Ref1
[0202] As a reference, a blank gypsum slurry without any dispersant was prepared using 300 g of plaster A and 0.10 g of accelerator (finely ground dihydrate from a ball mill) to adjust the setting time to 4:10 (minutes: seconds). The required amount of water corresponding to a water to binder (w / b) ratio of 0.660 and determined based on the untreated gypsum slurry was charged into a mixing container (agitator according to DIN EN 196-1), and then plaster A and accelerator were carefully sprayed into the water. In addition, Plast Retard L was added to the mixing water in an amount as shown in Table 1. The slurry was stirred at 285 rpm for 30 seconds. The water to binder (w / b) ratio was adjusted to 0.660 to achieve a flow rate of 20.6 cm of the reference example.
[0203] Other Examples of Table 1
[0204] The slurry was produced using 300 g of plaster A and 0.10 g of accelerator. The required amount of water corresponding to a water to binder (w / g) ratio of 0.660 and determined based on the untreated gypsum slurry was charged into a mixing container (agitator according to DIN EN 196-1), and then plaster A and accelerator were carefully sprayed into the water. Plast Retard L and the polymers described in Table 1 were added to the mixing water in the amounts indicated in Table 1. The slurry was stirred at 285 rpm for 30 seconds.
[0205] Table 1: Composition and properties of application examples with plaster A containing comparative building chemical composition and the present invention Invention of building chemical composition
[0206]
[0207] [% bws] = weight percentage of plaster
[0208] According to Table 1, the flow behavior of gypsum slurries prepared with reference dispersants with hydroxyl anchor groups (CE1.1 and CE1.3) is only slightly improved compared to the blank reference without dispersant (Ref1). The dispersant with only carboxyl anchor groups (CE1.2) shows good fluidization ability, however, the retardation is the highest, which is unfavorable.
[0209] The dispersants of the examples of the invention (IE1.1, IE1.2 and IE1.3) showed significantly improved fluidity compared to the reference (Ref1), as well as compared to polymer 2 with carboxyl anchoring groups (CE1.2). The results show that the comb polymers of the invention containing hydroxamic acid have fluidization ability in pure FGD plaster and moderate retarding ability.
[0210] Reference Example Ref2
[0211] As a reference, a blank gypsum slurry without any dispersant was prepared using 300 g of plaster B and 0.10 g of accelerator (finely ground dihydrate from a ball mill) to adjust the setting time to 4:20 (minutes: seconds). The required amount of water corresponding to a water to binder (w / b) ratio of 0.660 and determined based on the untreated gypsum slurry was charged into a mixing container (agitator according to DIN EN 196-1), and then plaster B and accelerator were carefully sprayed into the water. In addition, Plast Retard L in an amount as shown in Table 1 was added to the mixing water. The slurry was stirred at 285 rpm for 30 seconds. The water to binder (w / b) ratio was adjusted to 0.660 to achieve a flow rate of 19.0 cm of the reference example.
[0212] Other examples of Table 2
[0213] The slurry was produced using 300 g of plaster B and 0.10 g of accelerator. The required amount of water corresponding to a water to binder (w / g) ratio of 0.660 and determined based on the untreated gypsum slurry was charged into a mixing container (agitator according to DIN EN 196-1), and then plaster A and accelerator were carefully sprayed into the water. Plast Retard L and the polymers described in Table 2 were added to the mixing water in the amounts indicated in Table 2. The slurry was stirred at 285 rpm for 30 seconds.
[0214] Table 2: Composition and properties of application examples with plaster B containing comparative building chemical composition and the present invention Invention of building chemical composition
[0215]
[0216] [% bws] = weight percentage of plaster
[0217] According to Table 2, the gypsum slurries prepared with the reference dispersants (CE2.1 and CE2.3) have the same flow behavior compared to the blank reference without dispersant (Ref2). The dispersant with only carboxyl anchoring groups (CE2.2) shows a loss of fluidization ability in the presence of bentonite (clay) in the stucco.
[0218] The dispersants of the examples of the invention (I.E2.1 and IE2.2) show significantly improved fluidity compared to the reference (Ref2), as well as compared to the "classic" comb polymers containing only carboxyl anchor groups. The results show that the comb polymers of the invention containing hydroxamic acid also have fluidization capabilities in clay-contaminated FGD stucco.
[0219] For application in cementitious systems, polymers 8, 9 and 10 were tested in the compounds shown in Table 3. The dosage of polymer was adjusted to achieve a 28 ± 2 cm Conical flow. Determination of flow rate similar to DIN EN 1015-3. A cone (top d=70 mm, bottom d=100 mm, h=60 mm) was placed in the center of a dry glass plate of 400 mm diameter and filled with cement mortar. 5 minutes after the first contact between cement and water, the cone was lifted and the average diameter of the cake formed was determined. For the comb polymer of the invention containing hydroxamic acid anchoring groups (polymer 10), the polymer dosage with 0.13% bwoc was the lowest. However, the comparative polymers required higher dosages to achieve the same flux, such as 0.16% bwoc for the "classical" PCE comb polymer containing only carboxyl anchoring groups (polymer 9) and 0.17% bwoc for the comb polymer containing hydroxyl anchoring groups (polymer 8).
[0220] Table 3: Building material composition
[0221] Composition (mass) Function quantity Milke (CEM I 52,5N) OPC-Binder 40 servings Quartz sand (standard) filler 60 servings Polymer 8, 9 or 10 Superplasticizer (additive) Measure to 28 ± 2 cm DF 9010 Defoaming agent (additive) 0.05% bwoc water Start hydrating w / c**=0.35
[0222] *bwoc=weight of cement
[0223] **w / c = ratio of water to cement
[0224] Analogously to DIN EN 196-3, the setting start time (AB) and end time (AE) of the cement paste were determined using a Vicat needle instrument with a 300 g needle.
[0225] Polymer 8: AB: 236 minutes; AE: 323 minutes
[0226] Polymer 9: AB: 263 minutes; AE: 367 minutes
[0227] Polymer 10: AB: 245 minutes; AE: 300 minutes
Claims
1. A water-soluble polymer, comprising a) a main chain, the main chain consisting of at least A carbon chain of 16 carbon atoms, and b) polyether side chains, It is characterized in that A hydroxamic acid group or a salt thereof is attached to the backbone.
2. The water-soluble polymer according to claim 1, wherein the polyether side chain of the water-soluble polymer is a polyether group of structural unit (I), *-U-(C(O)) k -X-(AlkO) n -W (I) in * indicates the bonding site with the acid group-containing polymer, U is a chemical bond or an alkylene group having 1 to 8 carbon atoms, X is oxygen, sulfur or the group NR 1 , k is 0 or 1, n is an integer, the average value of which is in the range of 3 to 300 based on the acid group-containing polymer, Alk is a C2-C4 alkylene group, and in the group (Alk-O) n In, Alk can be the same or different, W is hydrogen, C1-C6 alkyl or aryl, or a group YF, wherein Y is a straight or branched chain alkylene group having 2 to 8 carbon atoms and can have a benzene ring, F is a 5- to 10-membered nitrogen-containing heterocyclic ring which is bonded via the nitrogen and which, as ring members, besides the nitrogen and carbon atoms, can also have 1, 2 or 3 additional heteroatoms selected from oxygen, nitrogen and sulfur, the nitrogen ring members being able to have radicals R 2 , and 1 or 2 carbon ring members can be present in the form of a carbonyl group, R 1 is hydrogen, C1-C4-alkyl or benzyl, and R 2 It is H, C1-C4 alkyl or benzyl.
3. The water-soluble polymer according to claim 1 or 2, wherein the water-soluble polymer is a copolymer comprising the structural unit (Va) in R 3 and R 4 are independently hydrogen, an aliphatic hydrocarbon group having 1 to 20 carbon atoms, a cycloaliphatic hydrocarbon group having 5 to 8 carbon atoms or an optionally substituted aryl group having 6 to 14 carbon atoms R 5 is H, -COOM a , -CO-NH-(OM a ), -CO-O(C q H 2q O) r -R 3 , -CO-NH-(C q H 2q O) r -R 3 M is hydrogen, a monovalent, divalent or trivalent metal ion, an ammonium ion or an organic amine. a is 1 / 3, 1 / 2 or 1 q occurs at every occurrence and for every (C q H 2q O) units are independently 2, 3 or 4 in the same or different manner, and r is 0 to 200.
4. The water-soluble polymer according to any one of claims 1 to 3, wherein the water-soluble polymer is a copolymer comprising the structural unit (Vb) R 6 , R 7 and R 8 are independently hydrogen, an aliphatic hydrocarbon group having 1 to 20 carbon atoms, an alicyclic hydrocarbon group having 5 to 8 carbon atoms or an optionally substituted aryl group having 6 to 14 carbon atoms, and U, k, X, Alk, n and W have the meanings as described for structural unit (I).
5. The water-soluble polymer according to claim 1 or 2, wherein the polymer is a polycondensation product comprising (II) structural units containing aromatic or heteroaromatic groups and the polyether groups, (III) A structural unit containing a hydroxamic acid group or a salt thereof and an aromatic or heteroaromatic moiety.
6. The water-soluble polymer according to claim 5, wherein the structural units (II) and (III) are represented by the following general formula: (II) A-U-(C(O)) k -X-(AlkO) n -W in A are identical or different and are represented by a substituted or unsubstituted aromatic or heteroaromatic compound having 5 to 10 carbon atoms in the aromatic system, U, k, X, Alk, n and W have the meanings as described for structural unit (I), (III) in D are identical or different and are represented by a substituted or unsubstituted aromatic or heteroaromatic compound having 5 to 10 carbon atoms in the aromatic system, in E is a chemical bond or -(C(O)) k -X-(AlkO) n -Z- in X is oxygen or the group NR 9 , k is 0 or 1, n is an integer, the average value of which is in the range of 0 to 100 based on the acid group-containing polymer, Alk is a C2-C4 alkylene group, and in the group (Alk-O) n In, Alk can be the same or different, R 9 is H, C1-C4 alkyl or benzyl Z is a C1-C3 alkylene group.
7. The water-soluble polymer according to claim 5 or 6, wherein the polycondensation product comprises an additional structural unit (IV) represented by the following formula: (IV) wherein each Y is independently the structural unit (II), the structural unit (III) or another component of the polycondensation product, and Each R 5 and each R 6 is independently H, CH3, COOH or a substituted or unsubstituted aromatic or heteroaromatic compound having 5 to 10 carbon atoms.
8. A water-soluble polymer according to any one of claims 1 to 7, wherein the average ratio of the number of moles of hydroxamic acid groups or salts thereof of the polymer to the total molar mass of the polymer is from 1 / 200 mol / (g / mol) to 1 / 2000 mol / (g / mol), wherein cations associated with the comb polymer, including protons, are not taken into account in calculating the total molar mass of the polymer.
9. The water-soluble polymer according to any one of claims 3 and 4, wherein the copolymer has an average molar weight (Mw) determined by gel permeation chromatography of between 2 000 g / mol and 200 000 g / mol.
10. The water-soluble polymer according to any one of claims 5 to 7, wherein the polycondensation product has an average molar weight (Mw) determined by gel permeation chromatography of between 3 000 and 150 000 g / mol.
11. The water-soluble polymer according to any one of claims 1 to 10, which is in the form of a powder. 12 . An inorganic particle composition comprising the water-soluble polymer according to claim 1 .
13. The inorganic particle composition according to claim 12, wherein the composition comprises an inorganic binder or an inorganic pigment.
14. The inorganic particle composition according to claim 12 or 13, wherein the composition comprises 0.005 wt% to 3 wt% of the water-soluble polymer based on the total dry weight of the inorganic particles.
15. Use of the water-soluble polymer according to any one of claims 1 to 11 as a dispersant in an inorganic particle composition.
Citation Information
Patent Citations
Melamine-formaldehyde condensates with a low formate content
DE19538821A1
Additives for hydraulic cement mixtures and method for preparing an easily dispersible hydraulic cement mixture
DE2007603A1
Sulphanilic acid-contg. melamine-formaldehyde] condensate prepn.
DE4411797A1
Process for producing highly-concentrated low-viscosity aqueous solutions of melamine-aldehyde resins and their use as additives for building materials
EP0059353B1
Use of salts of water soluble condensation products of naphthalene sulfonic acid and formaldehyde as an additive for inorganic binders and building materials
EP0214412B1